Purchase, consumption, and ownership of chickens and chicken products among households in Maputo, Mozambique: A cross-sectional study - Kayoko Shioda; Frederica Smith; Hermógenes Neves Mucache; Anushka Reddy Marri; Jhanel Chew; Karen Levy; Matthew C. Freeman (One Health)
Background: Chickens are an important source of animal protein, nutrition, and income in many low- and middle-income countries (LMICs). They are also a major reservoir of enteropathogens that contribute to the burden of illnesses among children. Food systems present a risk for transmission of enteropathogens from poultry to humans, but there is a lack of population-level data on the pattern of purchase, ownership, and consumption of live chickens and their products in LMICs to better characterize that risk. Methods: To assess chicken purchase, ownership, and consumption practices, we conducted a population-based survey using a structured questionnaire in Maputo, Mozambique in 2021. Multi-stage cluster sampling was used to obtain a representative sample of households in our study area. To minimize sampling bias and ensure a representative sample, we applied survey weighting using district-level population data and estimated weighted population-level values. Results: Heads of 570 households in Maputo completed our survey. Approximately half of these households purchased broiler chicken meat (weighted percentage of households: 44.8 %) and eggs (46.5 %) in the previous week of the survey date, while indigenous chicken meat was less popular (1950, 1.1 %). The most common source of chicken products was corner stores (i.e., small convenience shops on streets), followed by wet markets. Live chickens were raised by 15.6 % of households, and chicken feces were observed on the floor or ground at the majority of these households during house visits. Discussion: Our findings suggest that poultry provides a major source of animal protein in this setting. Given the predicted growth of poultry farming in LMICs in the coming decades, implementing One Health-based food safety measures at primary sources of chicken products, such as corner stores and wet markets, will be critical to controlling zoonotic pathogen transmission risks.